Ben Jonson : a life - Donaldson, Ian, 1935- (Oxford, England ; New York : Oxford University Press, 2011)
Ben Jonson was the greatest of Shakespeare's contemporaries. His fame rests not only on the numerous plays he had written, but on his achievements over three decades as principal masque writer to the early Stuart court, where he had worked in creative, if at times stormy, collaboration with Inigo Jones. One of the most accomplished poets of the age, he was, in fact if not in title, the first Poet Laureate in England. This biography draws on freshly discovered writings by and about Ben Jonson, and locates his work within the social and intellectual contexts of his time, and it depicts a life full of drama. Jonson's early satirical play, The Isle of Dogs, landed him in prison, and brought all theatrical activity in London to a temporary, and very nearly permanent, standstill. He was "almost at the gallows" for killing a fellow actor after a quarrel, and converted to Catholicism while awaiting execution. He supped with the Gunpowder Conspirators on the eve of their planned coup at Westminster. After satirizing the Scots in Eastward Ho! he was imprisoned again, and throughout his career was repeatedly interrogated about plays and poems thought to contain seditious or slanderous material. Throughout this biography, the auithor provides the fullest picture available of Jonson's personal, political, spiritual, and intellectual interests, and he discusses all of Jonson's major poetry and drama, plus some newly discovered works. Jonson emerges from this study as a more complex and volatile character than previously depicted, and as a writer whose work strikingly foresees the modern age.
The Biographer's Bones -- Scotland 1618-1619 -- Debatable Land 1542-1572 -- Influences 1572-1588 -- Conflicts 1588-1592 -- Entering the Theatre 1594-1597 -- Saved by the Book 1597-1598 -- Global Satire 1598-1601 -- The Wolf's Black Jaw 1601-1603 -- Scots, Plots, and Panegyrics 1603-1605 -- Following the Plot 1605-1607 -- Employment 1607-1610 -- Communities 1607-1612 -- Travels 1611-1613 -- Fame 1613-1616 -- Money 1614-1617 -- Scholarship 1619-1630 -- Growing Old 1619-1626 -- Dying Late 1626-1637 -- Remembrance with Posterity.
National Library’s N copy is signed by the author, 23 April 2016.
Includes bibliographical references and index.
Keywords: Jonson, Ben, -- 1573?-1637.; Authors, English -- Early modern, 1500-1700 -- Biography; Dramatists, English -- Early modern, 1500-1700 -- Biography; Australian